Effection of calcium phosphate tribofilm on anti-shudder performance in ATFs. (April 2018) - Li, Shaohui; Di, Zechao; Zhao, Zhiyu; Liu, Yang; Xu, Jingjing; Cui, Haitao; Huang, Dongsheng; Liu, Zhongguo; Li, Yang
Abstract: The anti-shudder performance of automatic transmissions (AT) is highly dependent on automatic transmission fluids (ATFs). Additives of ATFs interact with the steel surfaces to form tribofilms to provide AT with the desired properties. Hence, establishing the relationship between the tribofilm and friction characteristics is the key issue for optimizing the anti-shudder performance. This paper evaluates the tribological response of the calcium phosphate tribofilm in a disk-on-disk friction test apparatus (Wazau), which is used to simulate the clutch friction process. The changes of the tribofilm during friction and the variations of the μ-v curves with the tribofilms were discussed. Results showed that the calcium phosphate tribofilm contributed to maintain the anti-shudder property.